Use of carbon dioxide as a contrast medium for arteriography and intravascular ultrasound in endovascular prothesis of an abdominal aneurism in a patient with renal insufficiency. A case report - Bautista Sanchez, Fernando (2019)
The endovascular aortic replacement (EAR) is a minimally invasive technique for the treatment of abdominal aortic aneurisms. Despite of being a very useful technique it is restricted in patients with advanced chronic kidney disease and in patients allergic to iodine based contrast. The objective of this report is to describe the safe and effective use of arteriography using carbon dioxide combined to intravascular ultrasound in the endovascular aortic replacement of an aortic aneurism in a patient with renal insufficiency and history of allergy to iodine based contrasts. A review of the clinical chart of a patient who underwent this procedure was performed.